Experimental and Simulative Investigation of Deterministic Lateral Displacement and Dielectrophoresis Methods for Continuous Multi-Property Particle Sorting - Jonathan Kottmeier; Maike Sophie Wullenweber; Zhen Liu; Ingo Kampen; Arno Kwade; Andreas Dietzel (Powders)
Simulative and experimental studies were carried out to address multi-dimensional particle fractionation of non-biological particles according to size, shape, and density inside a high-throughput DLD array. Density sensitive separation was achieved for melamine and polystyrene particles at a diameter of 5 µm at a Reynolds number (Re) of 82, corresponding to an overall flow rate of 11.3 mL/min. This process is very sensitive, as no fractionation occurred for Re = 85 (11.7 mL/min). For the first time, the fractionation of elliptical polystyrene particles (5 × 10 µm) at Re > 1 was investigated up to Re = 80 (11 mL/min). A separation of elliptical particles from spherical melamine particles (5 µm) was observed in single experiments at all investigated Reynolds numbers. However, the separation is not reliably repeatable due to partial clogging of ellipsoidal particles along the posts. In addition, higher concentrations of polydisperse silica suspensions were experimentally investigated by using polydisperse silica particles at concentrations up to 0.4% (m/V) up to Re = 80 (20 mL/min). The separation size generally decreased with increasing Reynolds number and increased with increasing concentration. Separation efficiency decreased with increasing concentration, independent of the Reynolds number. In order to investigate the material-dependent separation in a contactless dielectrophoresis system (cDEP), the resolved CFD-DEM software was extended to calculate dielectrophoretic forces on particles. With this, the second stage of a serial-combined DLD-DEP system was simulated, showing good separation at lower flow rates. For these systems, different fabrication methods to minimize the distance between the electrodes and the fluid as well as the requirement to withstand high-throughput applications, were investigated.